Aromatic polyesters containing pendant azido groups: synthesis, characterization, chemical modification and thermal cross-linking - Nagane, Samadhan S.; Verma, Savita; Tawade, V, Bhausaheb; Sane, Prakash S.; Dhanmane, Sushilkumar A.; Wadgaonkar, Prakash P. (European Polymer Journal, 2019)
A partially bio-based bisphenol containing pendant azido group viz., 4,4'-(5-azidopentane-2,2-diyl) diphenol (AZBPA) was synthesized starting from 4,4'-bis (4-hydroxyphenyl) pentanoic acid. AZBPA was reacted with isophthaloyl chloride (IPC), terephthaloyl chloride (TPC) and a mixture of IPC/TPC (50:50 mol%) by phase transfer-catalyzed interfacial polycondensation route to obtain aromatic polyesters containing pendant azido groups. Copolyesters containing pendant azido groups were also synthesized by polycondensation of different molar proportions of AZBPA and commercially available 4,4'-(1-phenylethane-1,1-diyl) diphenol (BPA-AP) with IPC. Inherent viscosities and number average molecular weights of (co)polyesters were in the range 0.85-1.64 dL/g and 58,900-190,400, respectively, indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these polyesters. X-Ray diffraction analysis showed that (co)polyesters were amorphous in nature. (Co)polyesters were characterized using FT-IR, H-1 NMR spectroscopy, XRD, TGA and DSC analysis. The chemical modification of a representative copolyester containing pendant azido groups was carried out quantitatively using copper-catalyzed azide-alkyne cycloaddition (CuAAC) with two alkynes viz., phenyl acetylene (PA) and ethynyl-4-nitrobenzene (ENB). Additionally, (co)polyesters containing pendant azido groups were thermally cross-linked (170 degrees C/12 h) leading to the formation of network structures based on azide to nitrene decomposition and subsequent reactions on polyester backbone. The selected cross-linked polyesters were characterized by stress-strain measurements. The cross-linked polymers exhibited higher tensile strength and Young's modulus and lower % elongation at break compared to corresponding pristine polyesters containing pendant azido groups.
Keywords: Aromatic polyester; Chemical modification; Click chemistry; Pendant azido group; Thermal cross-linking

Partially bio-based furyl-functionalized organosoluble poly(ether ether ketone)s - Kuhire, Sachin S.; Talanikar, Aniket A.; Tawade, V, Bhausaheb; Nagane, Samadhan S.; Wadgaonkar, Prakash P. (Polymer International, 2021)
A new series of partially bio-based (co)poly(ether ether ketone)s bearing pendent furyl groups was synthesized by nucleophilic aromatic substitution polycondensation of varying molar proportions of 4,4 `-(furan-2-ylmethylene)bis(2-methoxyphenol) and bisphenol-A with 4,4 `-difluorobenzophenone. The chemical structures, compositions and random nature of (co)poly(ether ether ketone)s were confirmed by NMR spectroscopy. Inherent viscosities and number-average molecular weights of the (co)poly(ether ether ketone)s were in the range 0.74-2.90 dL g(-1) and 33 500-46 300 g mol(-1), respectively, indicating the formation of reasonably high molecular weight polymers. (Co)poly(ether ether ketone)s were readily soluble in common organic solvents and could be cast into tough, transparent and flexible films from chloroform solutions. (Co)poly(ether ether ketone)s exhibited 10% weight loss and glass transition temperatures in the range 429-464 and 152-156 degrees C, respectively. A representative copoly(ether ether ketone) was crosslinked with 1,1 `-(methylenedi-1,4-phenylene)bismaleimide via Diels-Alder reaction to form a crosslinked polymer which showed improved mechanical properties and was recycled twice without significant loss of mechanical properties. Diels-Alder/retro Diels-Alder reaction was demonstrated by studies of sol-gel transformation, solubility tests, DSC and stress-strain measurements. (c) 2020 Society of Chemical Industry
Keywords: aromatic poly(ether ether ketone)s; bio-based; crosslinking; Diels-Alder reaction; pendent furyl groups